Does borrowers' impatience disclose their hidden information about default risk? - Daniel Kraus (Universität Rostock, Institut für Volkswirtschaftslehre, 2013)
This chapter provides new evidence on borrowers' hidden information about their riskiness and its link to their impatience. To do so, I analyze consumer loans on the German platform Smava, which has a unique peer-to-peer lending process. Observationally identical but unobservably riskier borrowers offer investors a higher interest rate. This helps them to obtain their loan faster and with a higher probability. Very impatient borrowers who use Smava's instant loan service pay a higher interest rate and have a higher default risk than less impatient borrowers. These findings suggest that borrowers' impatience can be used to screen their riskiness.
Keywords: G21; D82; 330; Asymmetric Information; Financial Intermediation; Consumer loans; Patience